Clinical spectrum of AKI in chronic liver diseases - Purohit, Ashish; Pahawa, Naresh; Vohra, Rubina; Goswami, S.; B., Raju; Malviya, V.; Shukla, V.; Parashar, S.; Mishra, A.; Agrawal, A. (International Journal of Medical Research and Review, 2019)
Introduction: Acute kidney injury (AKI) is a heterogeneous syndrome of different aetiologies, and often multifactorial. Occurrence of Acute kidney injury in patients with chronic liver disease is frequent finding which makes prognosis of CLD even poorer. Material and methods: A prospective cohort observational study on 100 adult patients of chronic liver disease with AKI conducted over a period of 24 months from August 2016 to August 2018 at Sri Aurobindo medical college and postgraduate institute. Detailed clinical examination and biochemical tests were done. Univariate and multivariate logistic regression (odds ratio) analyses were used. Result: 87% are males and 13 % are females. The most common cause of cirrhosis is alcoholic 77% followed by hepatitis Bvirus related 10%, unknown etiology 7%, hepatitis C 3%, NASH 2%, Wilson 1. The most common sign of decompensation of liver is jaundice 78% followedby ascites 70%, hepatic encephalopathy 37% and upper GI bleed 30%. Distribution of child class as a prognostic indicator showed the maximum no. ofpatients found in class C 56% followed by class B 34% and class A 10%. Conclusion: Acute kidney injury is very common in chronic liver disease patient in our hospital and majority of them have intrinsic cause of AKI